The Status of Research into Resistance to Diet-Induced Obesity - Ding, C.; Guo, J.; Su, Z. (Hormone and Metabolic Research, 2015)
Obesity resistance is an increasingly popular area of study in academia, although the factors that lead to the occurrence of obesity resistance remain unclear. In this review, we discuss the currently known causes of obesity resistance. By comparing the differences between obesity-resistant individuals and obesity-susceptible individuals, researchers have identified the characteristics of obesity-resistant individuals. The primary approach has been to breed rats and mice with a high-fat diet and to compare the differences between obesity-resistant and obesity-susceptible individuals. The characterized differences have included gastrointestinal fat absorption, appetite, physical activity, fat storage, and fat consumption. Considerably more research is needed into the mechanisms of obesity resistance that could be used to lose weight among human subjects. However, there are few ongoing obesity resistance studies. Due to the relatively slow rate of development in this field, greater efforts must be applied in this area.
Keywords: obesity; obesity resistance; fat absorption; appetite; physical activity